The Legality of the Surrogate Mother Agreement Reviewed from Indonesian Civil Law - Yohanes I Wayan Suryadi; Ni Luh Made Mahendra Wati; I Wayan Wesna Astara; I Gusti Bagus Suryawan; Johannes Ibrahim Kosasih (APPTHI, 2025)
This research explores the legality of surrogate mother (uterus rental) agreements under Indonesian civil law, particularly given the absence of clear regulations governing such arrangements. The study aims to examine both the legal status of surrogate mother agreements and the legal status of children born through surrogacy, based on the provisions of the Indonesian Civil Code. This is a normative legal study employing a statutory approach, with secondary data collected through literature review and analyzed using descriptive-analytical methods. The findings indicate surrogate mother agreements are not legally valid under Indonesian civil law, as they fail to meet the essential requirements for a valid contract. The legal status of children born from such agreements depends on specific conditions. If the intended (biological) parents wish to establish a legal relationship with the child, they must go through an adoption process. Furthermore, the marital status of the surrogate mother determines the child’s legal status: (a) if the surrogate mother is legally married, the child is presumed to be the legitimate child of the surrogate and her spouse; (b) if the surrogate mother is unmarried or widowed, the child is considered to be born out of wedlock.